2022
DOI: 10.3389/fvets.2022.859025
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Fetal Bovine Serum in the Culture of Mesenchymal Stromal Cells and Potential Alternatives for Veterinary Medicine

Abstract: Fetal bovine serum (FBS) remains widely used as a supplement in cell culture media used in the isolation and expansion of mesenchymal stromal cells (MSC) despite longstanding practical, clinical, and ethical concerns over its use. As a result, research on alternative culture media supplement solutions that conserve crucial MSC characteristics has become increasingly relevant. Species-specific supplements and serum-free media such as platelet lysate or chemically defined media have been assessed for their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 94 publications
(160 reference statements)
1
24
0
4
Order By: Relevance
“…In comparison with complete medium control, RPMItreated cells exhibited a lower rate of viability (p< 0.00001) in MTT assay and less proliferation rate in CFSE-based proliferation analysis, however, in a lower extent compared with 96 h-SPS solution. These findings were expected as serum plays some known and unknown pivotal roles in animal cell culture including cancer cells (39). Thus, serum deprivation could induce LA7 cell death and reduce the cell viability to almost 50% in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…In comparison with complete medium control, RPMItreated cells exhibited a lower rate of viability (p< 0.00001) in MTT assay and less proliferation rate in CFSE-based proliferation analysis, however, in a lower extent compared with 96 h-SPS solution. These findings were expected as serum plays some known and unknown pivotal roles in animal cell culture including cancer cells (39). Thus, serum deprivation could induce LA7 cell death and reduce the cell viability to almost 50% in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…Studies have demonstrated that both healthy and immunosuppressed equine patients commonly have anti-FBS antibodies, likely due to regular vaccinations ( 14 ). Others have demonstrated that FBS proteins can be internalized by and/or bound to the extracellular matrix of the MSCs during culture ( 15 , 16 ). Even with methods that aim to remove FBS proteins, a detectable level of FBS proteins remain ( 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of cultured cells was evaluated using light microscopy. (Price and Gregory, 1982;Horn et al, 2010;Crespo-Diaz et al, 2011;Kinzebach et al, 2013;Shih and Burnouf, 2015;Pilgrim et al, 2022). (bFGF = basis fibroblast growth factor, EGF = epidermal growth factor, HGF = hepatocyte growth factor, VEGF = vascular endothelial growth factor, PDGF = platelet derived growth factor, IGF = insulin like growth factor, CCL = chemokine (C-C motif) ligand, CXCL = C-X-C motif chemokine ligand).…”
Section: Immunomorphological Characterization Of In Vitro Expanded Mscsmentioning
confidence: 99%
“…In addition to these advantages, FCS and PL are made up of different components as indicated in Table 1 . It is important to note that the list of components in this table is not exhaustive as the scientific community agrees that both supplements are still not fully characterized and show–sometimes important - batch-to-batch variability ( Price and Gregory, 1982 ; Horn et al, 2010 ; Crespo-Diaz et al, 2011 ; Kinzebach et al, 2013 ; Shih and Burnouf, 2015 ; Pilgrim et al, 2022 ). When considering all these factors, it can be assumed that the expansion culture protocol, including the growth medium can have major influence on the biological MSC characteristics.…”
Section: Introductionmentioning
confidence: 99%